Protein composition analysis of human plasma-derived and recombinant human serum albumin preparations based on 4D label-free proteomics - Li Ma; Peng Jiang; Zongkui Wang; Qing Liu; Jun Xu; Lu Cheng; Pan Sun; Xi Du; Changqing Li (PeerJ)
Background Clinical therapeutic human serum albumin (HSA) preparations are typically derived from human plasma and contain various accompanying proteins (APs). Previous studies have documented extensively the disparities in post-translation modifications, redox states and antioxidant capacities among HSA preparations from different manufacturers. Most of these studies have focused primarily on albumin, and analyzing APs in HSA preparations and recombinant HSA (rHSA) was often neglected. Methods In this study, the APs in human plasma-derived HSA (pHSA) from six Chinese manufacturers and recombinant HSA (rHSA) from yeast and rice were identified and analyzed using a four-dimensional (4D) label-free quantitative proteomic technology. Results A total of 456 different APs from the six pHSA preparations were identified, with 96 APs consistently detected in all pHSA samples. 52 APs from yeast-produced rHSA were identified, whereas 152 APs were detected in rice-expressed rHSA. Among the detected APs, haptoglobin, hemopexin and transthyretin were among the top eight APs with the highest relative abundance consistently observed in all pHSA preparations. Moreover, the results revealed that the identified APs in pHSA are primarily involved in endopeptidase inhibitor activity, complement and coagulation cascades, biosynthesis of amino acids and cholesterol metabolism by Gene Ontology (GO), Clusters of Orthologous Groups (COG)/euKaryotic Orthologous Groups (KOG), Kyoto Encyclopedia of Genes and Genomes (KEGG) and protein–protein interactions (PPI) annotation. The ELISA validation results confirmed the presence of haptoglobin, hemopexin, transthyretin and serotransferrin in pHSA but not in rHSA, aligning with the findings from the 4D label-free quantitative proteomic analysis.